Crashers - Haynes, Dana (Minotaur Books, 2010)
When a passenger plane, a Vermeer One Eleven, slams into the ground outside Portland, Oregon, a team--the "crashers"-- is quickly assembled to investigate the cause. Usually the team has months to determine the cause of a crash. But this time it's different. This time, the plane was brought down deliberately, without leaving a trace, and this was only a trial run.